Structure of Colloidal Flocs in relation to the Dynamic Properties of Unstable Suspension - Yasuhisa Adachi; Azusa Kobayashi; Motoyoshi Kobayashi (International Journal of Polymer Science)
Dynamic behaviors of unstable colloidal dispersions are reviewed in terms of floc formation. Geometrical structure of flocs in terms of chemical conditions and formation mechanics is a key to predict macroscopic transportation properties. The rate of sedimentation and rheological properties can be described with the help of fractal dimension (D) that is the function of the number of contacts between clusters (Nc). It is also well known that the application of water soluble polymers and polyelectrolytes, which are usually used as a conditioner or flocculants in colloidal dispersions, critically affects the process of flocculation. The resulted floc structure is also influenced by the application of polymer. In order to reveal the roles of the polymers, the elementary rate process of polymer reaching to colloidal interface and subsequent reconformation process into more stable adsorption state are needed to be analyzed. The properties of permeable flocs and adsorbed polymer (polyelectrolyte) layers formed on the colloidal surfaces remain to be worked out in relation to inhomogeneous porous structure and electrokinetics in the future.